Autofix – Automated Design of Fixtures. (May 2022) - Nambiar, S.; Albert, A. P.; Rimmalapudi, V. V. R. C.; Acharya, V.; Tarkian, M.; Kihlman, M.
Abstract: This paper presents a framework to develop the automated design of fixtures using the combination of design automation (DA), multidisciplinary optimization and robotic simulation. MDO necessitates the use of concurrent and parametric designs which are created by DA and knowledge-based engineering tools. This approach is designed to decrease the time and cost of the fixture design process by increasing the degree of automation. AutoFix provides methods and tools for automatically optimizing resource-intensive fixture design utilizing digital tools from different disciplines.